Stay Cool Don’t Be Cruel Psychoeducation Reduces Bullying Among Junior High Students: Psikoedukasi Stay Cool Don’t Be Cruel untuk Menurunkan Bullying pada Siswa SMP - Muhamad Dzaky Imansyah; Eko Hardiansyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Bullying remains a persistent problem in junior high schools and threatens students’ psychological well-being and social development. Specific Background: Schools require preventive interventions that address emotional regulation, empathy, and prosocial behavior rather than relying solely on disciplinary approaches. Knowledge Gap: Although psychoeducation has been widely recommended, evidence regarding the structured program “Stay Cool, Don’t Be Cruel: Upgrade Yourself, Not Put Down Your Friends!” in Indonesian junior high school settings remains limited. Aims: This study examined whether the psychoeducational program reduced bullying behavior among students at Muhammadiyah 5 Junior High School, Tulangan. Results: Using a one-group pre-test–post-test design, 30 eighth-grade male students were selected through purposive sampling and assessed using a bullying scale. Wilcoxon Signed Rank Test results showed a significant decrease in bullying behavior after the intervention (Z = -4.789, p = 0.000). Novelty: The program integrates interactive lectures, group discussions, educational games, role-play, emotion regulation training, and behavioral commitment within a four-session school-based intervention. Implications: The findings indicate that psychoeducation can serve as a practical preventive strategy for reducing bullying and fostering a safer, more inclusive school environment. Highlights: Significant reductions in bullying scores were observed after four psychoeducation sessions. The intervention combined emotional regulation, empathy building, and prosocial behavior training. School-based psychoeducation offers a practical preventive approach for safer student interactions. Keywords: Psychoeducation, Bullying Behavior, Emotion Regulation, Prosocial Behavior, Junior High School Students